'Until we have laws … everything is useless!': intersectionality, self-identified needs and inequity among sexual and gender minorities in Macedonia. Issue 10 (3rd October 2019) - Stojanovski, Kristefer; King, Elizabeth J.; Bondikjova, Viktorija; Brooks, Diarra K.; Mihajlov, Antonio
Abstract: There exists limited understanding about the intersectional nature of needs and inequities among sexual and gender minorities in Macedonia and Eastern Europe. We conducted a qualitative, cross-sectional and national needs assessment among 71 sexual and gender minority community members using semi-structured focus groups and interviews. Thematic analysis was used to better understand their self-identified needs, their concerns about equity and the intersectional nature of their needs. Community members discussed a wide range of health and healthcare needs as well as the social and structural factors that influence those needs, including: cultural norms; victimisation and safety concerns and the role of law, policy and politics; education and democratisation of knowledge; and economic and housing opportunities. Needs were patterned across different sexual and gender minority subgroups such that those experiencing heightened marginalisation (e.g. trans* persons) also experienced compounded forms of inequity. Given that sexual and gender minorities in Macedonia have numerous structurally induced intersectional needs, multilevel and multifaceted strategies are needed to ensure that their rights and needs are respected, protected and fulfilled at structural, community and individual levels.